2016
DOI: 10.1242/bio.021634
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the grades of a learned aversive-feeding response and the dopamine contents inLymnaea

Abstract: The pond snail Lymnaea learns conditioned taste aversion (CTA) and remembers not to respond to food substances that initially cause a feeding response. The possible relationship between how well snails learn to follow taste-aversion training and brain dopamine contents is not known. We examined this relationship and found the following: first, snails in the act of eating just before the commencement of CTA training were poor learners and had the highest dopamine contents in the brain; second, snails which had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Several other studies have suggested that the AAD activity is an additional source of regulation in the metabolism of monoamines. Independent regulation of 5-HT and 5-HTP content and similar accumulation of 5-HTP had been identified in the CNS of Lymnaea earlier, specifically, after food deprivation (Aonuma et al, 2016). Potentiation of L-DOPA effects in the presence of high dopamine concentration similarly suggests that AAD is inhibited by dopamine (Dyakonova et al, 2009).…”
Section: Differential Regulation Of Serotonin Metabolism During Exercsupporting
confidence: 56%
See 1 more Smart Citation
“…Several other studies have suggested that the AAD activity is an additional source of regulation in the metabolism of monoamines. Independent regulation of 5-HT and 5-HTP content and similar accumulation of 5-HTP had been identified in the CNS of Lymnaea earlier, specifically, after food deprivation (Aonuma et al, 2016). Potentiation of L-DOPA effects in the presence of high dopamine concentration similarly suggests that AAD is inhibited by dopamine (Dyakonova et al, 2009).…”
Section: Differential Regulation Of Serotonin Metabolism During Exercsupporting
confidence: 56%
“…Metabolites in the Pedal and Cerebral Ganglia of Lymnaea (Experiment 2) 5-HT and its precursor and catabolites were measured as described previously (Aonuma and Watanabe, 2012;Aonuma et al, 2016Aonuma et al, , 2017Aonuma et al, , 2018. Briefly, snails were quickly frozen using liquid N 2 , and the pedal and cerebral ganglia were dissected out of the ice-cold Lymnaea physiological solution.…”
Section: Measurement Of 5-ht and Itsmentioning
confidence: 99%
“…Altogether, the results based on behavioral and pharmacological studies support the existence of tight crosstalk among aversive and appetitive pathways. Interestingly, a similar interaction was also found in Lymnaea between dopamine level, which signals appetitive rewards, and the ability of animals to form a conditioned taste avoidance memory (34).…”
Section: Mutual Interference Between Appetitive and Aversive Memoriessupporting
confidence: 53%
“…Some psychological studies paid attention to the difference in the dopamine system between food-satiated and food-deprived states (Nader et al 1997). Recently, the effects of dopamine/ octopamine level on CTA-LTM were examined at various starvation states in Lymnaea (Aonuma et al 2016(Aonuma et al , 2017. Modestly food-deprived (Day 1) snails were the best learners and had significantly lower dopamine/octopamine levels compared to snails under the other conditions.…”
Section: Effects Of Monoamine Level On Cta-ltm In Snailsmentioning
confidence: 99%